Pemanfaatan Teknologi RESTFul Web Service pada Pengembangan Sistem Informasi Penilaian Probinmaba (Startup Academy) (Studi Kasus: Fakultas Ilmu Komputer Universitas Brawijaya) - Alfa Fadlilah; Issa Arwani; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The New Student Development Program (Startup Academy) is an introduction to campus life in the Faculty of Computer Science (FILKOM). Students who do not pass the Startup Academy cannot become members or administrators of Student Organizations in the Faculty of Computer Science. The difficulty in accessing this data has caused several institutions to continue recruiting students who did not pass Probinmaba (Startup Academy) because they did not know their graduation status. This caused the values ​​that were expected to be conveyed to new students in the Student Orientation to be meaningless and many laws were violated by the organization management and the new students themselves. Based on these problems, one effort that can be done is to build a system as an assessment information center that can help institutional administrators in accessing student graduation data. The system built also aims to make it easier for the executive committee to manage assessment data from year to year and general students to find out the details of the value and archive of their graduation certificates. The API that was built is intended for institutions that want to integrate the admission selection system for the management with existing graduation data. To test whether the system being developed meets the needs, a REST API, functionality, compatibility and usability test is carried out. The success rate of the test is 100% valid. This system is acceptable and according to user requirements.